Adverse Events Associated With Corticosteroid-Eluting Sinus Stents: A MAUDE Database Analysis. (January 2022) - Narwani, Vishal; Torabi, Sina J.; Kasle, David A.; Patel, Rahul A.; Lerner, Michael Z.; Manes, R. Peter
Objective: Corticosteroid-eluting stents (CESs) are increasingly used after endoscopic sinus surgery to reduce the need for revision surgery, but their use is not without risks. The objective of this study is to describe adverse events related to CESs. Study Design: Retrospective cross-sectional study. Setting: The US Food and Drug Administration's MAUDE database (2011-2020; Manufacturer and User Facility Device Experience). Methods: The MAUDE database was queried for reports of adverse events involving the use of CESs approved by the Food and Drug Administration, including Propel, Propel Mini, Propel Contour, and Sinuva (Intersect ENT). Results: There were 28 reported adverse events in total, with all events being related to the Propel family of stents and none related to Sinuva stents. Overall, 22 were categorized as patient-related adverse events and 6 as device-related events. The most common adverse event was related to postoperative infection, accounting for 39% (n = 11) of all complications. Four of these patients developed periorbital cellulitis, and 5 developed a fungal infection. The second-most common adverse event was migration of the stent, representing 21% of all complications (n = 6). Overall, 8 patients (29%) in our cohort required reintervention in the operating room, with subsequent removal of the CES. Conclusion: The most commonly reported adverse events were postoperative infection, including multiple cases of fungal infection, followed by migration of the stent. An increased awareness of the complications associated with CESs can be used to better inform patients during the consenting process as well as surgeons in their surgical decision making.